The leadership contract field guide : the personal roadmap to becoming a truly accountable leader - Molinaro, Vince, 1962- (John Wiley & Sons, Inc., 2018)
Providing a practical blueprint for implementing the Leadership Contract, this book offers activities, exercises and ideas for sustaining your impact as an accountable leader, and insights on how to leverage the leadership contract with your team and across your organization. --